A public health perspective on the responsibility of mass media for the outcome of the anti-COVID-19 vaccination campaign: the AstraZeneca case - Bianchi, F. P.; Tafuri, S. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
On February 9, 2021, the Italian Ministry of Health made the “Covid-19 vaccine AstraZeneca” (now “Vaxzevria”) available for use in the anti-COVID-19 vaccination campaign. However, in early March, the media reported that five people died a few days after receiving the vaccine. The reaction among both those already vaccinated and the vaccine candidates was one of near panic. The subsequent events have had long-lasting consequences, as 10–20% of vaccine candidates have since refused vaccination with the AstraZeneca vaccine, so in addition to the delay in vaccination, 200,000 doses of it were not administered. The goal of the vaccination campaign in Italy, when operating at full capacity, was to administer 500,000 doses per day, for a total of 3,500,000 doses per week. In this large amount of people, it is statistically certain that a certain number of subjects will develop non-vaccine related health problems or even die from causes unrelated to having been vaccinated. At this time in history, press reports must be inspired by a strong sense of responsibility and awareness of the potential consequences of misinformation; this is particularly true, especially because also the social media get inevitably involved.